البطل الإشكاليّ حامل إيديولوجيّا، قراءة في رواية "خيرة والجبال" لمحمد مفلاح - حورية, زيبوش; فاطمة, قسول (University of Eloued جامعة الوادي, 2024)
نسعى من خلال ورقتنا البحثيّة إلى تحليل بنية الشخصيّة في النصّ الرّوائي ومراحل التوالد الإيديولوجي من بداية السرد الحكائي الذي ظهرت فيه الشخصيّة البطلة مفرغة إيديولوجيّا إلى غاية نهاية السرد والّذي تبنّت فيه الشخصيّة وعيا غيّر مجرى حياتها ومن حولها من الناس، كما غيّرت مجرى السرد وطوّرت مراحله إلى أن بنت الشخصيّة البطلة وعيها الكامل وأصبحت المرأة الثوريّة ( قطبا إيديولوجيّا) بعد العقبات الكثيرة الّتي تعرّضت لها وصراعها مع ذاتها والآخر إلى أن اتّصفت بصفات حقّقت كاريزما البطل الإشكالي(الحامل الإيديولوجيّ). We seek through our research paper to analyze the character’s structure in the novel and the stages of the ideological reproduction from the start of the narration. The protagonist occurred empty ideologically up until the end, where the character adapted a consciousness that changed the course of her life and the people around her. She also changed the course of the narration, developed its stages, until the protagonist built her complete consciousness, and became the revolutionary woman (ideological pole) after the many obstacles she went through and conflicts with herself and the other, till she was characterized with attributes that fulfilled the charisma of the problematic protagonist.
The Problematic Protagonist Carrier Of Ideology, A Reading Of The Novel “kheira And The Mountains” By “mohamed Meflah”
مقال. مجلة علوم اللغة العربية وآدابها . مج16 . ع.02. جامعة الوادي
Keywords: البطل; الإشكالي; الحامل; الإيديولوجيا; خيرة والجبال; Protagonist; Problematic; carrier; Ideology; Kheira and the Mountains.